2006
DOI: 10.1523/jneurosci.2364-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Distribution of TrkB Receptors before, during, and after Synapse Formation between Cortical Neurons

Abstract: Although brain-derived neurotrophic factor (BDNF) potently regulates neuronal connectivity in the developing CNS, the mechanism by which BDNF influences the formation and/or maintenance of glutamatergic synapses remains unknown. Details about the subcellular localization of the BDNF receptor, TrkB, relative to synaptic and nonsynaptic proteins on excitatory neurons should provide insight into how BDNF might exert its effects during synapse formation. Here, we investigated the subcellular localization of tyrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 61 publications
8
89
1
1
Order By: Relevance
“…First, MNPs functionalized with a TrkB receptor agonist that stimulates neurite growth by activating TrkBdependent signaling pathways are endocytosed into RGC and DRG signaling endosomes and transported in nascent neurites between the soma and growth cones. These fMNP signaling endosomes are similar in size, transported at rates similar to Trk signaling endosomes in PC12 cells (30) and cortical neurons (31), and their transport did not affect growth cone motility or neurite growth rate on their own. Because signaling endosome dysfunction is linked to numerous nervous system diseases (19)(20)(21), fMNP signaling endosome studies may provide insight into targeting nanotherapeutics by identifying cargo-or domain-specific adaptor and motor proteins (32), and by identifying the effects nanoconjugation have on the endocytosis and trafficking of antireceptor agonist antibodies (33) that may impact nanotherapeutic efficacy.…”
Section: Discussionmentioning
confidence: 85%
“…First, MNPs functionalized with a TrkB receptor agonist that stimulates neurite growth by activating TrkBdependent signaling pathways are endocytosed into RGC and DRG signaling endosomes and transported in nascent neurites between the soma and growth cones. These fMNP signaling endosomes are similar in size, transported at rates similar to Trk signaling endosomes in PC12 cells (30) and cortical neurons (31), and their transport did not affect growth cone motility or neurite growth rate on their own. Because signaling endosome dysfunction is linked to numerous nervous system diseases (19)(20)(21), fMNP signaling endosome studies may provide insight into targeting nanotherapeutics by identifying cargo-or domain-specific adaptor and motor proteins (32), and by identifying the effects nanoconjugation have on the endocytosis and trafficking of antireceptor agonist antibodies (33) that may impact nanotherapeutic efficacy.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies reported that axonal trafficking organelles in general could contain multiple cargoes (25)(26)(27). TrkB, for instance, is transported with synaptic vesicle precursors to function in synapse formation (28). Other reports suggest that linker proteins connect cell adhesion molecules on the plasma membrane to intracellular transport vesicles to allow for a direct supply to nascent synapses after initial contact formation (29,30).…”
Section: Coupled Ampar/n-cadherin Trafficking Is Critical For Neuronalmentioning
confidence: 99%
“…Additionally, BDNF induces genes known to regulate synapse function, such as activity-regulated cytoskeletal (Arc) protein (10)(11)(12). Because the effects of BDNF on transcription are frequently explored by bath application, it is not clear if BDNF-mediated transcription is because of activation of TrkB in dendrites, axons, or the cell body (13). If dendritically localized TrkB receptors can regulate gene expression, mechanisms to convey the signal from dendrites to the nucleus, a distance that can be several hundred micrometers, would be required.…”
mentioning
confidence: 99%